EFFECT OF SUPERHEATING DEGREE AND PRESSURE ON EFFICIENCY OF AN ORES (ORGANIC RANKINE ENERGY STORAGE) SYSTEM - Júnior, M. M. D. O.; Maia, A. A. T.; Porto, M. P. (Revista de Engenharia Térmica, 2023)
The increased share of intermittent renewable energy sources has led to the development of new energy storage solutions to mitigate the effects of the variability of energy supply. CAES (Compressed Air Energy Storage) and LAES (Liquid Air Energy Storage) are two of the main solutions for medium to large-scale systems for long-term energy storage. However, both are limited; the first requires the availability of suitable geological formations and the second requires considerable investment because of the required liquefaction process. This work aims to evaluate the thermodynamic performance of an energy storage system, called Organic Rankine Energy Storage (ORES), with a focus on the effects of pressure and superheating degree at the expander inlet on the round-trip efficiency (i.e. ratio of generated energy during energy discharge over consumed energy during energy storage) of the system. The system was evaluated for six organic fluids which were selected based on commercial maturity, environmental impacts, and safety conditions, namely R-134a, R-152a, R-142b, R-236ea, R-365mfc, and R-141b. The efficiency of the system was obtained for each of those fluids using a steady-state model approximation of the operation of the system and for pressures at the expander inlet varying from 675 kPa up to 4,300 kPa (or 95% of the critical pressure, if lower) and for superheating degrees from 0 up to 40 K. The evaluation of the system for six organic fluids as working fluid resulted in round-trip efficiencies around 70 % (comparable to both CAES and LAES when subject to similar methodologies) with higher sensitivity to pressure than to superheating degree. For all fluids, an increase of 5 K in the superheating degree resulted in an absolute decrease of 2-5% in the round-trip efficiency. Effects of pressure were more diverse, R-152b, R-134a and R-142b showed an average reduction of 10% in efficiency for each reduction of 500 kPa in pressure (in the high efficiency operation region, while R-365mfc and R-141b were much less affected, around 5% decrease in efficiency for each reduction of 500 kPa. The fluids that had the highest efficiencies and that also presented a high efficiency for a wider range of pressures were the R141b and R365mfc, which are also the fluids with the highest critical temperatures.